Peran Penyuluh Agama Islam dalam Membina Kerukunan Antar-Organisasi Masyarakat Islam di Kecamatan Kambu Kendari - Heti Juningsih; Faizah Binti Awad; Nurdin; Muh. Ikhsan; Sitti Fauziah (Gunung Djati Conference Series, 2022)
This study aims to discuss the role of Islamic religious instructors in fostering harmony between Islamic community organizations in Kambu Kendari District. This research uses qualitative research with descriptive-analytical method. The formal object of this research is role analysis, while the material object is Islamic religious instructors in fostering harmony between Islamic community organizations in Kambu Kendari District. The results and discussion of this study include the objective conditions of harmony between Islamic religious instructors and Islamic community organizations in Kambu Kendari district, the steps taken by Islamic religious instructors, and the obstacles experienced by Islamic religious instructors in fostering harmony between Islamic religious instructors and Islamic community organizations in Kambu District. Kendari. This research is a relatively new research, so it is hoped that a more in-depth research will be conducted with a holistic approach.